From Science to Society New Trends in Environmental Informatics (Progress in IS,, 2018)
This book presents the latest findings and ongoing research in connection with green information systems and green information & communication technology (ICT). It provides valuable insights into a broad range of cross-cutting concerns in ICT and the environmental sciences, and showcases how ICT can be used to effectively address environmental and energy efficiency issues. Offering a selection of extended contributions to the 31st International Conference EnviroInfo 2017, it is essential reading for anyone looking to expand their expertise in the area.